Cosmic-ray positrons and negatrons of energies 10 to 250 MeV at 85 deg geomagnetic latitude - Cline, T. L.; Fichtel, C. E.; Kniffen, D. A. (1969)
Balloon measurements of cosmic ray positron and negatron intensities near North Pole